2017
DOI: 10.3390/w9120963
|View full text |Cite
|
Sign up to set email alerts
|

UV Disinfection of Hand-Rinse Greywater and Performance Testing Using Indigenous Staphylococcus spp.

Abstract: Greywater reuse is a feasible solution for decreasing raw water extraction in urban and rural settings. However, pathogen-specific performance guidelines and regulations have only recently been recommended; practical means to assess performance are missing. Here we examine the efficacy of Staphylococcus spp. as an endogenous surrogate for greywater pathogen reduction performance testing, by evaluating UV-C irradiation of hand-rinse greywater, and the variability in UV resistance between different wild Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted by (Eriksson et al, 2002;Ottoson & Stenstrom, 2003) revealed a large collection of excreta-related pathogens associated with greywater. Other studies have further identified a number of pathogens in greywater and these are Pseudomonas (Benami, Gillor, & Gross, 2015a;Khalaphallah & Andres, 2012), Legionella (Birks, Colbourne, Hills, & Hobson, 2004), Giardia (Birks et al, 2004;Birks & Hills, 2007), Cryptosporidium (Birks et al, 2004), and Staphylococcus Aureus (Benami et al, 2015a;Kim et al, 2009;Maimon et al, 2014;Shoults & Ashbolt, 2017) in greywater. Table 2.3 presents some selected biological parameters with their concentrations as reported in other studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted by (Eriksson et al, 2002;Ottoson & Stenstrom, 2003) revealed a large collection of excreta-related pathogens associated with greywater. Other studies have further identified a number of pathogens in greywater and these are Pseudomonas (Benami, Gillor, & Gross, 2015a;Khalaphallah & Andres, 2012), Legionella (Birks, Colbourne, Hills, & Hobson, 2004), Giardia (Birks et al, 2004;Birks & Hills, 2007), Cryptosporidium (Birks et al, 2004), and Staphylococcus Aureus (Benami et al, 2015a;Kim et al, 2009;Maimon et al, 2014;Shoults & Ashbolt, 2017) in greywater. Table 2.3 presents some selected biological parameters with their concentrations as reported in other studies.…”
mentioning
confidence: 99%
“…Table 2.3 presents some selected biological parameters with their concentrations as reported in other studies. (Atanasova et al, 2017;Friedler, Kovalio, & Ben-Zvi, 2006;Khalaphallah & Andres, 2012;Kim et al, 2009;Paulo, Begosso, Pansonato, Shrestha, & Boncz, 2009) Fecal coliforms Up to 1x10 6 (Halalsheh et al, 2008;Mandal et al, 2011;Masi et al, 2010) Pseudomonas aeruginosa 1.4x10 4 (Benami et al, 2015a;Khalaphallah & Andres, 2012) Staphylococcus aureus 1.2x10 2 -1.8x10 3 (Benami, Gillor, & Gross, 2015b;Kim et al, 2009;Maimon et al, 2014;Shoults & Ashbolt, 2017) Salmonella typhi 5.4x10 3 (Kim et al, 2009) Salmonella spp 3.1x10 3 (M. T Tr re ea at tm me en nt t s sy ys st te em ms s…”
mentioning
confidence: 99%